Doing Business 2014 : Understanding Regulations for Small and Medium-Size Enterprises - World Bank; International Finance Corporation (Washington, DC: World Bank Group, 2013)
Eleventh in a series of annual reports comparing business regulation in 185 economies, Doing Business 2014 measures regulations affecting 11 areas of everyday business activity: Starting a business, Dealing with construction permits, Getting electricity, Registering property, Getting credit, Protecting investors, Paying taxes, Trading across borders, Enforcing contracts, Closing a business, Employing workers.